Effect of Graphene Warm Abduction Orthosis on Hip Joint Development in Children with Spastic Cerebral Palsy - CUI Meiyu; LIU Jianjun; ZHANG Yan; ZENG Fanyong (康复学报)
ObjectiveTo observe the effect of graphene warm abduction orthosis on hip joint development in children with spastic cerebral palsy.MethodsA total of 28 children (56 hips) aged 2-10 years with spastic cerebral palsy were randomly divided into two groups by random number table method. There were 12 cases (24 hips) enrolled in the control group, 11 cases (22 hips) enrolled in the treatment group, and 5 cases (10 hips) withdrew from the study. Both groups received routine rehabilitation training. Additionally, the control group underwent adductor abduction traction training, and the treatment group wore graphene warm abduction orthosis. During the training, the adductor angle was at least >30°, the training time was 1-2 hours per day, and the treatment continued for 2 months. The migration percentage (MP), acetabular index (AI), neck shaft angle (NSA), gross motor function measure (GMFM) and modified Tardieu scale (MTS) were measured before and after treatment, and the differences were calculated.ResultsCompared with before treatment (47.67±3.56), the GMFM (49.9±13.08) after treatment in the control group significantly improved (P<0.05), and the change of MP, AI and MTS were not significant (P>0.05), and NAS (152.20±8.72)° was progressing (154.27±1.03)° (P<0.05). In the treatment group, MP, AI, GMFM and MTS after treatment were (26.82±12.44) %, [15.00 (13.75, 19.00)]°, (55.96±0.12), and (26.12±7.49)°, respectively, better than those before treatment (31.93±11.37) %, [17.50 (13.00, 13.00), 21.00)]°, (51.79±9.15), (19.09±8.93)°, the differences were statistically significant (P<0.05). There was no significant difference in NAS (152.20±8.72)° after treatment compared with that (154.27±1.03)° before treatment (P>0.05). The d-MP [3.75 (0.09,10.61)] %, d-NAS (2.28±9.54)° and d-GMFM (-3.80±1.97) of the treatment group were compared with those of the control group [0.00 (-3.70,2.80)] %,(-7.90±8.63)°, (-2.14±1.60), the differences were statistically significant (P<0.05), while the d-AI and d-MTS were not statistically significant (P>0.05).ConclusionThe graphene warm abduction orthosis can effectively improve hip dislocation or subluxation in children with spastic cerebral palsy, delay its progression, and improve the gross motor function.